NUMERICAL INVESTIGATION OF INTERACTION OF UNDERGROUND STRUCTURE (TUNNELS) WITH ELASTIC WAVES PROPAGATED IN GROUND MEDIUM - Gaynazarov Sultan; Rakhimdjanova Nodira (Journals Park Publishing, 2023)
In this article considers a dynamic method for calculating the analysis of an underground structure (tunnels) interacting with the soil environment. On the basis of numerical simulation, a diffraction pattern for an underground structure (tunnels) was constructed.
Keywords: finite element method, Newmark method, Bate method, stiffness matrix, damping matrix, mass matrix.